The marriage contract by contemporary channels of communication – A comparative study between jurisprudence theories and Iranian family law – - Gheshmi, Shamseddin Rostami (Journal of Islamic Sciences, 2021)
Marriage contract by contemporary means of communication is a marriage in which communication is carried out between the parties of the contract via the Internet. The channels are confined to writing, oral, or direct witnessing. This contract is one of the new conflicts in the matter of family law. The study followed the jurisprudential conditional method in order to derive the ruling on the marriage contract through these channels by presenting the opinions of the four jurisprudential schools of thought and the leading doctrine. Next, the study applied the descriptive analytical and comparative approach by mentioning, analysing, comparing, discussing, and then weighing the opinions. Then the relevant articles were mentioned in the Iranian Family Law. The research concluded with a set of results. The most important of which is that marriage through written, audio, or visual means of communication is permissible and does not differ in its validity from the direct and traditional marriage contract. Furthermore, all the conditions of the marriage contract stipulated in Iranian law do not oppose the marriage contract through modern channels of communication. Moreover, the only difference is in the use of modern channels of communication through which all the elements and conditions of marriage can be met. Accordingly, the legal articles related to this issue can be amended in the Iranian Family Law. The research recommended amending Article 1062 of the Iranian Family Law to include marriage by modern channels of communication and an electronic application is to be created for this purpose. The research has laid down the basics on which the application is based, such as a statement of scope of its use, its specifications, and other related matters.